HUMAN Resources Development. West Indian Commission Report : a time for action. (1994)
Suggests that CARICOM countries take deliberate steps towards the establishment of a single market for human resources, served by a common pool of workers of all levels of skills. Recommends the reform and strengthening of the education system at all levels, and the development of a scheme to attract highly skilled and professional people to the region.
DC